Comparative efficacy of short-term spinal cord stimulation and pulsed radiofrequency in zoster-associated pain: a stratified database study - Lu, Fan; Li, Jun; Zhong, Jiwei; Li, Xuehan; Song, Li; Ye, Ling; Xiao, Hong (Frontiers in Neurology, 2025)
BackgroundZoster-associated pain (ZAP) significantly impacts quality of life (QoL) and poses therapeutic challenges. However, there is limited comparative evidence on interventional strategies, particularly regarding short-term spinal cord stimulation (st-SCS) vs. pulsed radiofrequency (PRF), stratified by disease duration and dermatomal involvement.ObjectivesThis retrospective study aimed to compare the efficacy and safety of st-SCS and PRF in patients with ZAP, with the primary outcome defined as ≥50% pain reduction at 1 month post-treatment. Secondary outcomes included neuropathic pain characteristics, quality of life (QoL), medication use, and adverse events.MethodsClinical data were retrospectively extracted from the institutional pain management database at West China Hospital, covering the period between July 2022 and February 2024. Eligible patients had a clinical diagnosis of ZAP and received either st-SCS or PRF following standard clinical practice. Outcomes assessed included pain severity, neuropathic pain characteristics, QoL indicators, medication usage, and adverse events. Follow-up assessments occurred immediately post-treatment and at 1, 3, 6, and 12 months. Stratified analyses were performed according to disease duration and affected dermatomes.ResultsA total of 186 patients met the inclusion criteria (st-SCS, n = 96; PRF, n = 90). st-SCS showed superior pain relief compared to PRF, with significantly higher rates of ≥50% pain relief immediately post-treatment (72.92 vs. 14.44%, P < 0.001), at 1 month (46.88 vs. 31.11%, P = 0.035), and at 3 months (64.58 vs. 43.33%, P = 0.005). Stratified analysis indicated greater efficacy of st-SCS in patients with disease durations of 1–2 months and thoracic dermatomal involvement, showing significantly lower NRS scores across multiple follow-ups. Additionally, st-SCS significantly reduced neuropathic pain characteristics, with lower Douleur Neuropathique 4 (DN4) scores at 1 month (1.77 ± 0.80 vs. 2.11 ± 0.99, P = 0.046), 3 months (1.42 ± 0.98 vs. 2.29 ± 1.16, P < 0.001), and 6 months (1.38 ± 0.93 vs. 1.81 ± 1.02, P = 0.008). QoL improvements were consistently greater with st-SCS, particularly regarding sleep quality, mood, and life enjoyment from 1 to 6 months post-treatment.Conclusionsst-SCS provides superior short-term and sustained pain relief and QoL enhancements compared to PRF in managing ZAP, especially in patients with shorter disease duration and thoracic and abdominal involvement. Both treatments demonstrated comparable safety profiles, confirming the viability and effectiveness of st-SCS as an advantageous interventional option for managing zoster-associated pain.